Geology, mineralogy and geochemistry of the Holmsletfjella Au-As occurrence, West Spitsbergen Fold Belt, Svalbard - Simonsen, Håvard Kvåle (Universitetet i Tromsø, 2012)
Holmsletfjella is situated on the southern side of St. Jonsfjorden on the archipelago of Svalbard. The drill core herein studied is part of an exploration program by Store Norske. Chemical analysis of the drill cores in combination with the geological history have reviled the Holmsletfjella Formation and the Ultramafic Vestgötabreen Complex to have been altered by fluids migrating through the rocks during the formation of the Caledonian mountain chain. These fluids were sourced from VAMSNAZ (V, As, Mo, Se, Ni, Ag and Zn) shales, which is an excellent source of gold. At the same time as the fluids were migrating the serpentinites of the Ultramafic Vestgötabreen Complex underwent listwanite alteration that resulted in partial alteration of the serpentinites into listwanites. Possible gold deposits may have been displaced or remobilised during the generation of the West Spitsbergen Fold Belt thereby making the work locating the gold deposits harder.